Lidar Range-Resolved Optical Remote Sensing of the Atmosphere - Weitkamp, Claus (Springer Series in Optical Sciences,, 2005)
Written by leading experts in optical radar, or lidar, this book brings all the recent practices up-to-date and covers a multitude of applications, from atmospheric sciences to environmental protection. Its broad cross-disciplinary scope should appeal to both the experienced scientist and the novice in the field. The Foreword is by one of the early pioneers in the area, Herbert Walther.